PERAN LINGKUNGAN KELUARGA DALAM MENINGKATKAN KESEHATAN MENTAL REMAJA - Yulianti Yulianti; Nur Fadila; Chairrun Nisa; Indah Multia Cahyani; Sri Chantika putri Zalianti; Dhetalia Okta Riyani; Dila Puspita Sari (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Mental health is a state of well-being in which a person is able to endure the rest of life, work well, and affect society. Mental health does not only mean the absence of mental disorders, but also includes a person's ability to manage their emotions, social and interpersonal relationships, and adapt to change. Conflict in the family can affect children's behavior and mental health, because the family is the closest place for a child. What children see and hear often runs in the family. Therefore, it is a good thing that family activities and the child's personality, behavior and health are influenced by what their parents see and hear. Mental disorders are still common in Indonesia, and it needs to be addressed more, because it is the young generation who will be the children and grandchildren of the country one day. If a teenager has a mental health problem and is left untreated, the child's mental health problem will persist and hinder their development. The purpose of this research is to find out the prevalence of mental health problems among teenagers today, the factors that affect them, and how the family can affect the mental health of teenagers in Indonesia. As you said, the role of the family in supporting children's mental health is very important, because parents are the main source of income for children. They can provide emotional support, create a safe environment, and help children develop problem-solving and social skills. By understanding the role of the family environment, we can better understand how to improve the mental health of the younger generation.